Role of Mesenchymal Stem Cells on Cornea Wound Healing Induced by Acute Alkali Burn - Yao, Lin; Li, Zhan-rong; Su, Wen-ru; Li, Yong-ping; Lin, Miao-li; Zhang, Wen-xin; Liu, Yi; Wan, Qian; Liang, Dan (PLOS ONE, 2012)
The aim of this study was to investigate the effects of subconjunctivally administered mesenchymal stem cells (MSCs) on corneal wound healing in the acute stage of an alkali burn. A corneal alkali burn model was generated by placing a piece of 3-mm diameter filter paper soaked in NaOH on the right eye of 48 Sprague-Dawley female rats. 24 rats were administered a subconjunctival injection of a suspension of 2×106 MSCs in 0.1 ml phosphate-buffered saline (PBS) on day 0 and day 3 after the corneal alkali burn. The other 24 rats were administered a subconjunctival injection of an equal amount of PBS as a control. Deficiencies of the corneal epithelium and the area of corneal neovascularization (CNV) were evaluated on days 3 and 7 after the corneal alkali burn. Infiltrated CD68+ cells were detected by immunofluorescence staining. The mRNA expression levels of macrophage inflammatory protein-1 alpha (MIP-1α), tumor necrosis factor-alpha (TNF-α), monocyte chemotactic protein-1 (MCP-1) and vascular endothelial growth factor (VEGF) were analyzed using real-time polymerase chain reaction (real-time PCR). In addition, VEGF protein levels were analyzed using an enzyme-linked immunosorbent assay (ELISA). MSCs significantly enhanced the recovery of the corneal epithelium and decreased the CNV area compared with the control group. On day 7, the quantity of infiltrated CD68+ cells was significantly lower in the MSC group and the mRNA levels of MIP-1α, TNF-α, and VEGF and the protein levels of VEGF were also down-regulated. However, the expression of MCP-1 was not different between the two groups. Our results suggest that subconjunctival injection of MSCs significantly accelerates corneal wound healing, attenuates inflammation and reduces CNV in alkaline-burned corneas; these effects were found to be related to a reduction of infiltrated CD68+ cells and the down-regulation of MIP-1α, TNF-α and VEGF.